Hubungan Pengetahuan Dan Sikap Dengan Perilaku Pencegahan Covid-19 Pada Pengendara Ojek Online Di Kota Pekanbaru - Fahmi Nofriandi; Ferianto Ferianto; Jeins Niverli Hendri; Bhukkar Adil Sjam (Jurnal Ilmu Kesehatan Abdurrab, 2023)
COVID-19 is a disease that attacks the respiratory tract which was first discovered in December 2019 to April 2022with a total of 6,046,0467 cases of people experiencing COVID-19, as many as 156,240 people died from COVID-19. This preventive behavior is influenced by the knowledge and attitudes of online motorcycle taxi drivers. Onlinemotorcycle taxi drivers are at high risk of experiencing COVID-19, this is due to mobilization and the high risk ofcontact with passengers. The knowledge, attitude, and behavior of online motorcycle taxi drivers regarding theprevention of COVID-19 is still the main thing to prevent transmission of COVID-19 during this pandemic.Objective: To find out the relationship between knowledge and attitudes to COVID19 prevention behavior amongonline motorcycle taxi drivers in Pekanbaru City.Methods: This study used an observational study design. analyticwith cross-sectional research design. The sampling technique was carried out by accidental sampling on onlinemotorcycle taxi drivers in Pekanbaru and statistically tested using a sperm test. The population of this studyamounted to 59 respondents.Results: There was a relationship between knowledge and COVID-19 prevention behavior among onlinemotorcycle taxi drivers in Pekanbaru in 2022 (p-value 0.000; r 0.444), with a moderate strength of relationship and apositive direction of association. There was a relationship between attitude and COVID-19 prevention behavioramong online motorcycle taxi drivers in Pekanbaru in 2022 (p-value 0.000; r 0.605), with a strong strength ofrelationship and a positive direction of association.